Glutathione-dependent extracellular ferric reductase activities in dimorphic zoopathogenic fungi - Zarnowski, Robert (2005)
In this study, extracellular glutathione-dependent ferric reductase (GSH-FeR) activities in different dimorphic zoopathogenic fungal species were characterized. Supernatants from Blastomyces dermatitidis, Histoplasma capsulatum, Paracoccidioides brasiliensis and Sporothrix schenckii strains grown in their yeast form were able to reduce iron enzymically with glutathione as a cofactor. Some variations in the level of reduction were noted amongst the strains. This activity was stable in acidic, neutral and slightly alkaline environments and was inhibited when trivalent aluminium and gallium ions were present. Using zymography, single bands of GSH-FeRs with apparent molecular masses varying from 430 to 460 kDa were identified in all strains. The same molecular mass range was determined by size exclusion chromatography. These data demonstrate that dimorphic zoopathogenic fungi produce and secrete a family of similar GSH-FeRs that may be involved in the acquisition and utilization of iron. Siderophore production by these and other fungi has sometimes been considered to provide a full explanation of iron acquisition in these organisms. Our work reveals an additional common mechanism that may be biologically and pathogenically important. Furthermore, while some characteristics of these enzymes such as extracellular location, cofactor utilization and large size are not individually unique, when considered together and shared across a range of fungi, they represent an important novel physiological feature.